Pressure Generated on a Simulated Mandibular Oral Analog by Impression Materials in Custom Trays of Different Design - Adel Al-Ahmad, DDS, MS;1 Radi Masri, BDS, MS, PhD;2 Carl F. Driscoll (Journal of Prosthodontics, 2006)
The purpose was to measure the pressure exerted under a simulated mandibular edentulous impression at different locations using commonly used impression materials and four impression tray configurations